2022
DOI: 10.1111/rda.14223
|View full text |Cite
|
Sign up to set email alerts
|

Yearling bulls have reduced sperm concentration and increased seminal plasma interleukin‐8 after a 28‐day breeding season

Abstract: We hypothesized that yearling bulls selected for a 28‐d breeding season would have reduced sperm concentrations and morphology, and have increased seminal plasma concentrations of pro‐inflammatory cytokine interleukin‐8 (IL‐8). Yearling bulls were selected based on a breeding soundness examination (BSE) at approximately 415 d of age and contained at least 750 million sperm in the ejaculate, with 12 bulls randomly selected for breeding (BREEDERS) and 12 bulls not selected for breeding (NON‐BREEDERS). After a 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…It has been reported that the potential fertility of a male is dependent on the interaction of multiple factors such as management, environment, and the individual’s own physical and reproductive conditions [ 47 ]. Moreover, when analyzing the data before and during the mating period, a similar effect to that described by Snider et al [ 57 ] can be observed, as sperm concentration decreases significantly during the mating period ( p < 0.05). These authors pointed out that the decline in sperm concentration is of great importance because males showing this effect may potentially be unable to fertilize with females in high male-to-female ratios during the mating season, affecting the pregnancy rate of the productive system.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It has been reported that the potential fertility of a male is dependent on the interaction of multiple factors such as management, environment, and the individual’s own physical and reproductive conditions [ 47 ]. Moreover, when analyzing the data before and during the mating period, a similar effect to that described by Snider et al [ 57 ] can be observed, as sperm concentration decreases significantly during the mating period ( p < 0.05). These authors pointed out that the decline in sperm concentration is of great importance because males showing this effect may potentially be unable to fertilize with females in high male-to-female ratios during the mating season, affecting the pregnancy rate of the productive system.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding sperm concentration, studies on B. taurus crossbreeds aged between one and two years suggest that animals used during a 28-day breeding season tend to experience a decrease in sperm concentration and an increase in seminal plasma interleukin-8 levels at the end of the mating period [ 57 ]. In our work, the bulls were in breeding pastures, in pairs, for a period of twenty-one days, and the mating season extended for approximately eighty days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the age of 1 year, they have worse indicators of sperm production and sperm motility compared to older ones, although there is no difference in sperm motility after unfreezing cryopreserved sperm doses between younger and older bulls (Murphy et al, 2018). One-yearolds selected for breeding have not only reduced sperm production but also an increased inflammatory response, leading to poor reproduction if used intensively in breeding (Snider et al, 2022). Sexually mature bulls have betterquality sperm than young ones (Bhakat et al, 2011).…”
Section: Resultsmentioning
confidence: 99%